Resistance Training Variables for Optimization of Muscle Hypertrophy: An Umbrella Review - Bernárdez-Vázquez, Roberto; Raya-González, Javier; Castillo, Daniel; Beato, Marco (Frontiers in Sports and Active Living, 2022)
This umbrella review aimed to analyze the different variables of resistance training and their effect on hypertrophy responses, and to provide practical recommendations for the prescription of resistance training programs to maximize hypertrophy responses. A systematic research was conducted through of PubMed/MEDLINE, SPORTDiscus and Web of Science following the preferred reporting items for systematic reviews and meta-analysis statement guidelines. A total of 52 meta-analysis were found, of which 14 met the inclusion criteria. These studies were published between 2009 and 2020 and comprised 178 primary studies corresponding to 4784 participants. Following a methodological quality analysis, nine meta-analyses were categorized as high quality, presenting values of 81-88%. The remaining meta-analysis were rated as moderate quality, with values between 63-75%. Based on this umbrella review, we can state that the variables of volume, frequency, intensity, contraction type, repetition duration and the application of the restriction of blood flow could condition hypertrophy adaptations in healthy subjects. Conversely, other variables as, exercise order, time of the day and type of periodization appear not to directly influence the magnitude of muscle mass gains. These findings provide valuable information for the design and configuration of the resistance training program with the aim of optimizing muscle hypertrophy.